JOKOWI'S EMOTIONS ON INSTAGRAM FOLLOWING INDONESIA'S CANCELLATION AS U-20 WORLD CUP HOST - Silvanus Alvin (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, dan Pendidikan, 2023)
The cancellation of Indonesia as the host of the U-20 World Cup grabbed massive public attention. FIFA canceled due to rejection from various groups such as Bali Governor I Wayan Koster, Central Java Governor Ganjar Pranowo, several parties and mass organizations. President Jokowi also responded to this, starting from affirming that it is necessary to separate politics and sports, to expressing his enthusiasm after the cancellation by FIFA. This research seeks to find out what kind of emotions President Jokowi is trying to display on Instagram social media. Emotions and political communication have a close relationship, as both influence each other and shape public views on political issues. This qualitative research uses AWS Rekognition as a machine learning-based visual analysis tool to determine the emotions displayed. The result of the research is that Jokowi shows a calm emotion. One of the logical assumptions for showing calm emotions is to maintain stability and show that the President is in control of the situation.